"A Stage-Hand, Perhaps": Life as a Stage Play in John Banville's the Book of Evidence. Issue 5 (19th October 2020) - Pietrzak, Wit
ABSTRACT: In the present essay, the focus is laid on literary allusions in The Book of Evidence, as I argue that the novel thematizes Freddie Montgomery's consistent exploration of the ways in which he might endow the world around him with at least a transient order and meaning. It is as part of this quest that he repeatedly adverts to the view of life as a performance analogic to a theater play. I will further suggest that the allusions are specifically to Macbeth and the eponymous hero's soliloquy in Act V when he learns of Lady Macbeth's demise.